2015
DOI: 10.4317/jced.51716
|View full text |Cite
|
Sign up to set email alerts
|

Indirect sinus lift without bone graft material: Systematic review and meta-analysis

Abstract: A systematic literature review and a meta-analysis of indirect sinus lift without the use of bone graft material was performed. A PubMed search was made from January 2005 to January 2012 with keywords: “sinus lift”, “osteotome”, “graft” and “maxillary sinus elevation”. The inclusion criteria were: maxillary sinus lift technique with osteotomes with a minimum follow-up period of 5 months after surgery without bone graft material. 11 articles were included. The mean gain in residual crestal bone height after max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
3
23
0
1
Order By: Relevance
“…Based on these facts, it is indicated that bone grafts are not mandatory for a successful MSFA, as long as we could maintain the integrity of Schneiderian membrane and obtain a stabilized chamber for bone regeneration 50 . Studies focused on non-grafted TSFE have been performed and confirmed that such technique is reliable for MSFA sites, even in cases with limited residual bone height (RBH) 51 . Considering the longevity of non-grafted TSFE, some studies have even shown that there were no differences in implant survival rates between bone substitutions grafted and non-grafted TSFE sites 8,11 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Based on these facts, it is indicated that bone grafts are not mandatory for a successful MSFA, as long as we could maintain the integrity of Schneiderian membrane and obtain a stabilized chamber for bone regeneration 50 . Studies focused on non-grafted TSFE have been performed and confirmed that such technique is reliable for MSFA sites, even in cases with limited residual bone height (RBH) 51 . Considering the longevity of non-grafted TSFE, some studies have even shown that there were no differences in implant survival rates between bone substitutions grafted and non-grafted TSFE sites 8,11 .…”
Section: Discussionmentioning
confidence: 92%
“…In this study, initially we analyzed the implant survival rate (ISR) within non-grafted TSFE studies among different RBH, and no significant differences were observed on 1-year ISR among groups with different average RBH within non-grafted TSFE group, even cases with limited RBH (<4 mm) obtained favorable 1-year ISR 51,60,61 . This confirmed that limited RBH does not impact the implant survival for non-grafted TSFE surgeries, as long as secured primary stabilities are obtained on implants 51,60,61 . Furthermore, the increase in bone-implant contact area and the compression of bone during TSFE augments the bone density around implant sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, too, have reported success rates up to 90% for osteotome sinus lift technique[15161718] as the least and highest rates of success rates were 90.8% and 100%, respectively. Furthermore, in a study by Gabbert et al .,[19] a success rate of 94% was reported.…”
Section: Discussionmentioning
confidence: 99%
“…An implant osteotomy is made short of the maxillary sinus floor by about 2 mm and osteotomes are used to fracture up the sinus floor and particulate bone graft material is placed between the created implant osteotomy and the fractured sinus floor, resulting in increased eventual PMABH. This technique can be utilized without a bone graft as well [2]. Usually an implant is placed at the same time.…”
Section: Introductionmentioning
confidence: 99%